Incidence, Predictors, and Outcomes of Hospital‐Acquired Anemia. Issue 5 (1st May 2017) - Makam, Anil N.; Nguyen, Oanh K.; Clark, Christopher; Halm, Ethan A.
Abstract : BACKGROUND: Although hypothesized to be a hazard of hospitalization, it is unclear whether hospital‐acquired anemia (HAA) is associated with increased adverse outcomes following discharge. OBJECTIVE: To examine the incidence, predictors, and postdischarge outcomes associated with HAA. DESIGN: Observational cohort study using electronic health record data. SUBJECTS: Consecutive medicine discharges between November 1, 2009 and October 30, 2010 from 6 Texas hospitals, including safety‐net, teaching, and nonteaching sites. Patients with anemia on admission or missing hematocrit values at admission or discharge were excluded. MEASURES: HAA was defined using the last hematocrit value prior to discharge and categorized by severity. The primary outcome was a composite of 30‐day mortality and nonelective readmission. RESULTS: Among 11, 309 patients, one‐third developed HAA (21.6% with mild HAA; 10.1% with moderate HAA; and 1.4% with severe HAA). The 2 strongest potentially modifiable predictors of developing moderate or severe HAA were length of stay (adjusted odds ratio [OR], 1.26 per day; 95% confidence interval [CI], 1.23‐1.29) and receipt of a major procedure (adjusted OR, 5.09; 95% CI, 3.79‐6.82). Patients without HAA had a 9.7% incidence for the composite outcome versus 16.4% for those with severe HAA. Severe HAA was independently associated with a 39% increase in the odds for 30‐day readmission or death (95% CI, 1.09‐1.78). Most patients with severe HAA (85%) underwent a major procedure, had a discharge diagnosis of hemorrhage, and/or a discharge diagnosis of hemorrhagic disorder. CONCLUSIONS: Severe HAA is associated with increased odds for 30‐day mortality and readmission after discharge; however, it is uncertain whether severe HAA is preventable.